Tualang honey effects on high cholesterol diet induced nonalcoholic steatohepatitis in an animal model - Hamad Mohamed, Zenab B.; Hamad Alfarisi, Hamad Abdulsalam; Abdullah, Nor Zamzila; Harun, Norra; Muhammad, Naznin; Abdul Rahim, Roslina (World Journal Of Pharmacy And Pharmaceutical Sciences, 2018)
Aim: This study aimed to examine the effects of tualang honey against the high cholesterol diet induced biochemical and histological changes in the liver and pancreas. Methods: Female Sprague-Dawley rats were used, where the control group (n = 5) was fed with commercial rat pellet; the high cholesterol diet (HCD) group (n= 5) was given 12% cholesterol diet; while the HCD with tualang honey (HCD+TH) group (n =5) was fed with 12% cholesterol diet with daily 1.4 g/kg/day of tualang honey. Blood biochemical analysis were analysed at 1 week and 6 weeks. The liver and pancreas tissues were harvested at the end of 6 weeks for histological examination. Results: The cholesterol diet induction resulted in dyslipidaemia and abnormal liver function. The HCD+TH group have shown an increase in total cholesterol, LDL-c, ALP levels and decreased TG, HDL-c and AST levels significantly at the end of 6 weeks compared to HCD group. The mean plasma glucose level was elevated at 1 week in the HCD group. Plasma insulin levels were higher in HCD+TH group at both 1 and 6 weeks. The HOMA-IR was also higher at 1 week in the HCD+TH group. The liver histology of both HCD and HCD+TH groups showed steatohepatitis with minimal hepatocyte degeneration while the pancreatic sections revealed no abnormalities. Conclusion: The cholesterol diet of 6 weeks duration in this study did induce some features of NASH with dyslipidaemia with abnormal liver profile. Low dose of Tualang honey supplementation exhibited no effect on dyslipidaemia and histopathological changes.